Factibilidad de crear una empresa para confeccionar y comercializar Ropa Deportiva Unisex, en la ciudad de Loja. - Tenezaca Ojeda, Kerly Yomar (2024)
The feasibility project involves analyzing a new product's acceptance and potential success in the market. To achieve this, the project was based on the following objectives: market study to determine supply, demand, unmet demand, and marketing plan, as well as a marketing plan; a technical study to determine the size, location, and engineering of the project; an organizational study to determine the legal and administrative structure; and a financial study to understand investments, financing, cost and income projections, financial statements, and financial evaluation. The research approach was quantitative, using a deductive method with exploratory and descriptive scope. Techniques and instruments were used for data collection. In the supply and demand analysis, it was found that there was an unmet demand of 109,619 units in the first year, despite having an installed capacity of 17,520 units. The production cost in the first year was $13.06, with a sales price of $16.33, leading to a total sales revenue of $67,924.49. The break-even point was determined to be 64% of the installed capacity, with a sales target of $43,464.45. Cash flow analysis resulted in the following evaluation indicators: NPV of $37,352.90; IRR of 37.27%; payback period of 2 years, 9 months, and 2 days; benefit-cost ratio of 1.25. Additionally, sensitivity analysis supported a cost increase of 16.80% and a revenue decrease of 15,80%. Following this comprehensive analysis, the project was deemed feasible.